2021
DOI: 10.1111/ijcp.14998
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of carbapenem‐resistant Acinetobacter baumannii isolated from three major hospitals in Jordan

Abstract: Background: In the last decade, incidences of carbapenem-resistant Acinetobacter baumannii have been increasingly reported worldwide. Consequently, A. baumannii was included in the World Health Organization's new list of critical pathogens, for which new drugs are desperately needed. The objective of this research was to study the molecular epidemiology and antimicrobial susceptibility of clinical carbapenemresistant A. baumannii isolated from Jordanian hospitals. Methods: A total of 78 A. baumannii and 8 Acin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…All examined Acinetobacter isolates carried bla OXA-51 gene which is a confirmed intrinsic gene in A. baumannii [ 23 , 43 ]. OXA-23 was the commonest carbapenemase gene among these isolates, found in (98.5%) of isolates, in agreement with previous studies in Jordan [ 13 , 44 , 45 ] but higher than Obeidat et al 2014 (58%) [ 15 ]. Moreover, studies in Egypt and Qatar showed that 100% of the isolates were positive for bla OXA-23 [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…All examined Acinetobacter isolates carried bla OXA-51 gene which is a confirmed intrinsic gene in A. baumannii [ 23 , 43 ]. OXA-23 was the commonest carbapenemase gene among these isolates, found in (98.5%) of isolates, in agreement with previous studies in Jordan [ 13 , 44 , 45 ] but higher than Obeidat et al 2014 (58%) [ 15 ]. Moreover, studies in Egypt and Qatar showed that 100% of the isolates were positive for bla OXA-23 [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a number of isolates investigated in this study belonged to ST40, ST2, and ST602. A. baumannii strains belonging to these STs were previously isolated in Jordan from clinical samples (Ababneh et al 2021b) and intensive care unit environmental surfaces (Ababneh et al 2021a). This suggests a possible transmission of these isolates from the hospital sewage to the vegetable and fruit samples through irrigation water, or by crosscontamination from handling personnel who might be infected or colonized with A. baumannii.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, the analysis of 86 A. baumannii and Acinetobacter species isolates from three major hospitals in 2018 showed that 90.6% of them were carbapenem-resistant, with expression of the bla OXA-51-like (89.5%), bla OXA-23-like (88.3%), and bla NDM-1 (10.4%) genes. The number of extensively drug-resistant (XDR) isolates was reportedly ‘alarming’ [ 38 ]. Hayajneh et al used non-linear time-series methods to inform antibiotic policies to determine a threshold for third-generation cephalosporin and carbapenem use in a 533-bed tertiary teaching hospital in Irbid.…”
Section: Resultsmentioning
confidence: 99%